Expanding the Market for MSMEs Keripik Tempe in Denpasar City through Digital Marketing Strategies with an Empowerment-Based PAR Approach - Wardani, Kadek Devi Kalfika Anggria; Artnat, Diwan Sanjaya; Gorda, Anak Agung Ngurah Eddy Supriyadinata (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This Community Service activity aims to expand the marketing scope of the MSME keripik tempe